If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 4(2x + 8) = -8 + 8(x + 8) Reorder the terms: -4x + 4(8 + 2x) = -8 + 8(x + 8) -4x + (8 * 4 + 2x * 4) = -8 + 8(x + 8) -4x + (32 + 8x) = -8 + 8(x + 8) Reorder the terms: 32 + -4x + 8x = -8 + 8(x + 8) Combine like terms: -4x + 8x = 4x 32 + 4x = -8 + 8(x + 8) Reorder the terms: 32 + 4x = -8 + 8(8 + x) 32 + 4x = -8 + (8 * 8 + x * 8) 32 + 4x = -8 + (64 + 8x) Combine like terms: -8 + 64 = 56 32 + 4x = 56 + 8x Solving 32 + 4x = 56 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 32 + 4x + -8x = 56 + 8x + -8x Combine like terms: 4x + -8x = -4x 32 + -4x = 56 + 8x + -8x Combine like terms: 8x + -8x = 0 32 + -4x = 56 + 0 32 + -4x = 56 Add '-32' to each side of the equation. 32 + -32 + -4x = 56 + -32 Combine like terms: 32 + -32 = 0 0 + -4x = 56 + -32 -4x = 56 + -32 Combine like terms: 56 + -32 = 24 -4x = 24 Divide each side by '-4'. x = -6 Simplifying x = -6
| L+50=1.32 | | -8/9(9+y)=64 | | 5/3x+1/3x=8/3+8/3x | | -8(t-7)-7(2t+1)=-17 | | 7(x-4)=6(x+1)-3 | | 5(40-(40-x))+10(40-x)+25x=405 | | -59=-5(4a-4)+1 | | -x-(13+4x)=-3(5-9k)+2 | | -0.8(2x-6)=1.7(3-x) | | 3y+(-11y)= | | 12x^2-81x-3/7=0 | | x/3-9=11 | | 12x^2-81x-3/7 | | -15t-9+8t=4t-3 | | 4+-1x=-1x+4 | | 0.5x-0.1=0.4-0.6(9-2x) | | 3y-7=2y+5 | | 3-6x=-80-5x | | 4+-1x=1x+4 | | x^2+1x=272 | | -2y+8=3y+28 | | 6x^24= | | 3x+1.5x+x+180=455 | | 6(4x-3)-10= | | 7x+9x-69=46-7x | | 2(9x-1)=99-7(3-4k) | | 8n-3.5=-20 | | z/2+1=7z/2 | | 10(1+30b)=-20 | | 2x+8-k=-3 | | 24-4= | | 20z+80=140+10x |